An approach to the perception of risk before smoking in university students - Llopiz Guerra, Karel (My University, 2018)
The current challenges of university education commit to the faculty of universities to make their best effort to meet the aspiration of converting new generations, social beings trained and prepared to prevent them in the future become consumer citizens of tobacco and achieve rejection of this habit, which will allow a better preventive culture that contributes to education for health, improve the quality of life of all and become better examples before the new generations who will have the responsibility to educate through the educational process designed for Cuban schools, which conceives an organized system to offer an educational response adjusted to the diversity of the university student, such as those who are in risk groups due to having tobacco users in the social environment in which they operate. The proposal is to provide each student with the pedagogical help they need, in addition to proceeding with all the factors, directed from the school health department and the anti-drug commission, drawing actions to eradicate and mitigate this situation which allows the achievement of an adequate perception of risk before smoking.
Keywords: Perception of Risk; Prevention; Tobacco; Educational Program Education